A Study on the Characteristics of Microseismic Signal during Deformation and Failure of Different Materials under Uniaxial Compression - Chengwu Li; Xiaomeng Xu; Lihui Dong; Mohammad Sarmadivaleh; Xiaoyuan Sun (Shock and Vibration)
With the decline of shallow coal reserves and increase in demand of coal consumption, the hazard of coal and rock dynamic disasters is expanding. In this paper, we conducted some laboratory scale tests on coal, cement, and glass materials to figure out the microseismic (MS) characteristic differences among materials. A new method, denoted as WPT-LMD, is proposed to conduct signal denoising and analysis work. A series of basic analyses regarding MS are conducted, including the relationships between MS characteristics and loading rate, coal powder particle size, loading stage, and MS event statistics. Research results show that the damage of all these three materials is accompanied with MS events, abundant with low frequency component (0–200 Hz). But cement and coal specimens produce with relative wide frequency distribution in sample frequency domain, while glass specimens were found to only produce low frequency event. The powder particle sizes have obvious influence on the strength of coal specimen, but the loading rate seems to have no influence on the MS characteristics. The outcome of the paper will further provide a theoretical basis for understanding the mechanism of MS activities and has great significance to improve the coal mining safety.